ONTOLOGICAL APPROACH TO THE CONCEPT OF ARTIFICIAL INTELLIGENCE (Scientific journal of the Fergana State University, 2024)
The author of this article tries to explain the concept of artificial intelligence using an ontological approach. Traditional approaches to defining artificial intelligence have been limited to focusing on technical or functional aspects rather than the fundamental nature of intelligence. Based on ontology - as a branch of philosophy that studies the nature of existence - the authors suggest that it is possible to achieve a broader understanding of artificial intelligence. They propose to consider artificial intelligence as a form of ontology, defined by a set of ontological categories that describe the nature and properties of intelligent systems.